The Challenges of Being Chair in 2015: A 28 Year Perspective - Domenick J Pinto (Academic Chairpersons Conference Proceedings, 2015)
For 28 years as chair, I have witnessed the evolution of the role of chairperson as entrepreneurial skills, conflict resolution and time management have become increasingly vital to the success of the chair. My session will summarize the challenges that chairs must now face and overcome in 2015. The session will help relatively new and new chairs face scenarios and how to problem solve them.
Keywords: conflict; management; entrepreneur; time; leadership